2008
DOI: 10.1002/asi.20904
|View full text |Cite
|
Sign up to set email alerts
|

A quick MST‐based algorithm to obtain Pathfinder networks (∞, n − 1)

Abstract: Network scaling algorithms such as the Pathfinder algorithm are used to prune many different kinds of networks, including citation networks, random networks, and social networks. However, this algorithm suffers from run time problems for large networks and online processing due to its O(n 4 ) time complexity. In this article, we introduce a new alternative, the MST-Pathfinder algorithm, which will allow us to prune the original network to get its PFNET(∞, n − 1) in just O(n 2 · log n) time.The underlying idea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…White (2003) revisited the ACA study of information science with Pathfinder network scaling. A fast algorithm to compute Pathfinder networks is published in 2008 (Quirin et al, 2008).…”
Section: Expert Reviewmentioning
confidence: 99%
“…White (2003) revisited the ACA study of information science with Pathfinder network scaling. A fast algorithm to compute Pathfinder networks is published in 2008 (Quirin et al, 2008).…”
Section: Expert Reviewmentioning
confidence: 99%
“…A study conducted by Quirin et al showed that the pruning of a graph of 1000 nodes could take more than one hour on a modern computer [45]. Since these kinds of graphs are frequent in MAS debugging, a better response time is a critical aspect in the elaboration of a better interaction with the user.…”
Section: Variants Of the Pathfinder Algorithmmentioning
confidence: 98%
“…By definition, PFNETs are connected, so each element is linked to the rest [45]. We propose to use this property to address the first problem (about the intra and inter cluster visualization).…”
Section: The Pfnets Approach Vs the Clustering Approach For Mas Debumentioning
confidence: 98%
See 2 more Smart Citations